2021
DOI: 10.3389/fbioe.2021.628797
|View full text |Cite
|
Sign up to set email alerts
|

Volume of Surgical Freedom: The Most Applicable Anatomical Measurement for Surgical Assessment and 3-Dimensional Modeling

Abstract: Surgical freedom is the most important metric at the disposal of the surgeon. The volume of surgical freedom (VSF) is a new methodology that produces an optimal qualitative and quantitative representation of an access corridor and provides the surgeon with an anatomical, spatially accurate, and clinically applicable metric. In this study, illustrative dissection examples were completed using two of the most common surgical approaches, the pterional craniotomy and the supraorbital craniotomy. The VSF methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The AOF was calculated by the area within the 4 limiting posts at 14 cm from ACP, similar to previous studies. 13,20,21 The globe was retracted medially at 5 mm increments. For each globe translation, the new AOF and DOFs were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AOF was calculated by the area within the 4 limiting posts at 14 cm from ACP, similar to previous studies. 13,20,21 The globe was retracted medially at 5 mm increments. For each globe translation, the new AOF and DOFs were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Since then, several navigational stereotactic systems have been used to better define the DOF and AOF of keyhole approaches. [12][13][14][15] Moe et al specifically analyzed surgical movements in the cranial keyhole operations and found that at least 18 DOF between 2 instruments is needed to be efficiently used. 16 To achieve this DOF in TORPEDO, the ocular globe is retracted medial or inferior depending on the pathology.…”
mentioning
confidence: 99%
“…The novel method developed in this laboratory was used to calculate the VSF specific to critical intracranial anatomy for the pterional and supraorbital approaches. 8 In addition to this, the craniocaudal and mediolateral AOAs were assessed in degrees. As previously described, the AOAs in these planes are defined as the maximum allowable AOA in the vertical and horizontal planes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The VSF accounts for multiple inaccuracies in the practical and mathematical method of assessment, and it enables the production of spatially and anatomically accurate 3D models. 8 The VSF is a preferable and clinically applicable standard for the estimation of surgical freedom, defined as an instrument's ability to move specific to the surgical corridor. An assessment of the pterional and supraorbital approaches with use of this novel method has never been completed.…”
mentioning
confidence: 99%
“…The volume of surgical freedom (VSF) is defined as the maximal available working volume with respect to a specific surgical corridor and STS. 22 The VSF was developed to provide a threedimensional (3D) spatially and anatomically accurate quantitative and visual representation of a surgeon's instrument freedom. This standardized metric allowed for a direct comparison of approach-specific and visualization-specific surgical maneuverability regardless of variability in data collection methodology.…”
Section: Volume Of Surgical Freedommentioning
confidence: 99%